Was there a '4.2ka event' in Great Britain and Ireland? Evidence from the peatland record - Roland, TP; Caseldine, CJ; Charman, DJ; Turney, CSM; Amesbury, MJ (Quaternary Science Reviews, 2014)
This is the author accepted manuscript. The final version is available from the publisher via the DOI in this record. Palaeoenvironmental and archaeological data from several regions around the world show evidence of a multi-centennial climatic event occurring approximately 4200cal yr BP (4.2ka). Whilst the climatic change and/or impact of the 4.2ka event is clear in certain regions, such as western Asia, evidence for the event has yet to be fully evaluated in northwest Europe. This study presents high-resolution, multi-proxy palaeoclimate records from sites in Northern Ireland, ideally located for an objective examination of the nature of the event in Great Britain and Ireland within the broader context of mid-Holocene climate change c. 6.5-2.5ka. The peatlands of northwest Europe possess considerable potential for the examination of climatic change in the North Atlantic region, demonstrated by the range of palaeohydrological proxy data generated during this study (peat humification, plant macrofossil and testate amoebae analyses) supported by a high-resolution chronology (including comprehensive AMS 14 C and tephrochronology). The inter-site testate amoebae reconstructions appear coherent and were combined to produce a regional climatic record, in marked contrast to the plant macrofossil and peat humification records that appear climatically complacent. The testate amoebae reconstruction, however, provides no compelling evidence for a 4.2ka event signal and is consistent with previously reported studies from across northwest Europe, suggesting the origin and impact of this event is spatially complex. © 2013 Elsevier Ltd. This research was carried out while T.P.R. held a UK Natural Environment Research Council studentship (NE/G524328/1) at the University of Exeter. .